HCV protease inhibitors: using the evidence to guide clinical practice. (September 2012) - Yu, Derek; Feld, Jordan J
The development of direct-acting antivirals with activity against hepatitis C virus (HCV) has been a major breakthrough. The Phase III clinical trials of the protease inhibitors boceprevir and telaprevir have shown that both of these agents substantially improve rates of sustained virological response in patients with genotype 1 HCV infection. However, both agents must be combined with pegylated-IFN and ribavirin and come with their own new, additional side effects. In this review, the data from the clinical trials are reviewed and practical points about using the HCV protease inhibitors in clinical practice are discussed, including: dosing, treatment regimens for naive and experienced patients, the role of a 4-week lead-in phase, the utility of IL-28B testing, drug–drug interactions and antiviral resistance. Major take home messages are highlighted at the end of each section.